Photosynthetic Light Reactions in Chemically Fixed Anacystis nidulans, Chlorella pyrenoidosa, and Porphyridium cruentum - Hallier, U. W. (1969)
The photochemical activities of various species of unicellular algae (Anacystis nidulans, Chlorella pyrenoidosa, and Porphyridium cruentum) were studied following chemical fixation. Fixation with formaldehyde and glutaraldehyde yielded cells which retained their ability to perform photosystem I and photosystem II reactions. The photochemical efficiencies of some fixed algae are as great as those of unfixed spinach chloroplasts. Fixed algae containing accessory pigments appear to be useful models for further studies of the light reactions of photosynthesis.